2019
DOI: 10.1101/695064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxytocin increases after affiliative interactions in male Barbary macaques

Abstract: 14Mammals living in stable social groups often mitigate the costs of group living through the 15 formation of social bonds and cooperative relationships. The neuropeptide hormone 16 oxytocin (OT) has been proposed to promote both bonding and cooperation although only 17 a limited number of studies have investigated this under natural conditions. Our aim was to 18 assess the role of OT in bonding and cooperation in male Barbary macaques (Macaca 19 sylvanus). First we tested for an effect of affiliation -groomin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Overall we found a high probability that urinary OT levels are elevated following grooming interactions in adult male Barbary macaques. This is generally in line with previous studies showing a positive relationship between OT and grooming (primates: Benítez et al, 2018;Crockford et al, 2013;Snowdon et al, 2010;vampire bats, Desmodus rotundus: Carter and Wilkinson, 2015), as well as other socio-positive interactions more generally (primates: Preis et al, 2018;Benítez et al, 2018;Snowdon et al, 2010;Wittig et al, 2014;vampire bats: Carter and Wilkinson, 2015;dogs: Romero et al, 2014). Given the low number of grooming between non-bonded partners in our study, we could not test partner specific effects of grooming.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Overall we found a high probability that urinary OT levels are elevated following grooming interactions in adult male Barbary macaques. This is generally in line with previous studies showing a positive relationship between OT and grooming (primates: Benítez et al, 2018;Crockford et al, 2013;Snowdon et al, 2010;vampire bats, Desmodus rotundus: Carter and Wilkinson, 2015), as well as other socio-positive interactions more generally (primates: Preis et al, 2018;Benítez et al, 2018;Snowdon et al, 2010;Wittig et al, 2014;vampire bats: Carter and Wilkinson, 2015;dogs: Romero et al, 2014). Given the low number of grooming between non-bonded partners in our study, we could not test partner specific effects of grooming.…”
Section: Discussionsupporting
confidence: 91%
“…Questions still remain under which contexts OT release is partner specific. It has been suggested that in smaller social groups, all group members are bonded to a sufficient degree to elicit OT release after affiliative interactions (Benítez et al, 2018), whereas in larger groups variance in affiliation rates may be large enough that OT release may only occur after affiliations with more closely bonded partners. Such an explanation would be consistent with observed differences in partner specificity of OT release between chimpanzee populations (Crockford et al, 2013;Preis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations